Residual mechanical, durability and microstructural performance of consortium bio-concrete under elevated temperatures - Priya S Nair; Rajesh Gupta; Vinay Agrawal; Thandiwe Sithole; Blessen Skariah Thomas (Results in Engineering)
This study investigates the mechanical, durability, and microstructural properties of post-fired pineapple leaf fiber (PALF)-reinforced bacterial wollastonite concrete (FR-BWC) exposed to elevated temperatures of 200, 400, 600, 800, and 1000 °C. Consortium Bacillus cohnii and Bacillus sp. at pH 10 (without urea addition) facilitated microbial-induced calcium carbonate precipitation (MICCP). Alkali-treated PALF fibers (5–20 mm; 0.25–1 %) were incorporated. Spalling occurred at 1000 °C in fibered samples, while control specimens exhibited spalling at 800 °C. The maximum compressive strength reduction was 44.56 % and 36.61 % at 1000 °C and 800 °C, respectively, with 20 mm fibers showing the highest strength loss (up to 55.71 % at 1000 °C). Weight reduction between 800 °C and 1000 °C ranged from 0.37 % to 1.41 %, with higher fiber content (0.75–1 %) accelerating weight loss. Post-heated specimens exhibited an average wear depth increasing from 1.07 mm (ambient) to 3.36 mm (800 °C). At 800 °C, the highest moisture reduction of 61.3 % was observed in 1F20, while the lowest reduction of 43 % was recorded in BWC .The residual UPV values remained excellent (E) up to 800 °C and good (G) at 1000 °C. Acid-treated specimens displayed minimal weight loss < 2.5 % at 14 days and < 6 % at 28 days. SEM-EDS, XRD, and FTIR analyses confirmed significant calcium carbonate precipitation and the presence of other cementitious products. Residual specimens maintained satisfactory durability features despite marginal weight loss and compressive strength reduction at 800 °C. The integration of wollastonite enhanced thermal resistance, making FR-BWC a durable, high-performance composite for extreme conditions.